Urgent care dermatology symptom-based diagnosis - Fitzpatrick, James E. 1948-; High, Whitney A.; Kyle, W. Lamar (Elsevier, 2018)
Urgent Care Dermatology: Symptom-Based Diagnosis, by Drs. James E. Fitzpatrick, Whitney A. High, and Lamar Kyle, helps you quickly identify skin conditions and provide necessary treatment at the point of care. Concise, to-the-point text is highlighted by more than 1,000 high-quality photographs - all conveniently organized by lesion appearance - making this resource ideal for first-line clinicians to quickly identify and treat dermatologic conditions